IATROGENIC CUSHING SYNDROME AND HYPERTENSION IN AN INFANT GIRL DUE TO USE OF NAPPY RASH CREAM CONTAINING A POTENT TOPICAL STEROID - Gillani, Saima; Danish, Burhan Ali; Shah, Syed Faiz Muhammad; Hussain, Fawad; Aziz, Farida; Iqbal, Attiya (Journal of Ayub Medical College Abbottabad, 2020)
Eleven months old female patient presented to paediatric out patient with parents concerned about her facial swelling. Upon examination child’s weight and height for age were normal on her percentiles, she had a cushingoid facies with plethoric cheeks (Figure-1,2) though generalized oedema was absent and there was centripetal obesity with some muscle wasting (Figure-3,4). Systemic examination was normal excluding blood pressure which was high for her age. Electrolytes and cortisol levels were normal. On further inquiry it was revealed that she had been using a nappy rash cream containing a potent steroid, i.e., fluticasone for 2 months and this was identified as a cause for her cushingoid features. Keywords: Cushingoid face; Topical steroids; Paediatric hypertension